Evaluation of Fermented Rain Tree Seed Meal as an Alternative Protein Source: Effects on Growth, Nutrient Utilization, Digestive Enzyme Activity and Digestibility in Tilapia, Orechromis niloticus: Fermented Rain Tree Seed Meal as Alternative Protein Source - Dileep, Namitha; Pradhan, Chiranjiv; Peter, Nikhila (Fishery Technology, 2025)
Microbial fermentation improves the nutritional value of plant ingredients by decreasing the natural toxicants and reducing the complexity of the nutrients. The current study was conducted to replace soybean meal (SM) with yeast (Saccharomyces cerevisiae) fermented rain tree seed meal (FRTSM) and to evaluate its effect on the growth, nutrient utilisation, carcass composition, digestive enzymes activity, and degree of digestion of tilapia fry (Oreochromis niloticus). Five iso-nitrogenous and iso-lipidic diets were formulated with replacing SM (0, 25%, 50%, 75% and 100%) with FRTSM and was denoted as FRTSM0 (Control, without FRTSM), FRTSM25, FRTSM50, FRTSM75 and FRTSM100. The feeding experiment was conducted for 60 days in FRP tanks of 150L capacity taking twenty tilapia fry (6.27±0.09 g) per tank in triplicates. The tilapia fed with FRTSM0 diet showed significantly higher (P<0.001) final weight, weight gain and weight gain percentage compared to other treatments. The quadratic regression analysis showed that replacing up to 37 and 38.64% of SM with FRTSM led to optimal specific growth rate (SGR) and weight gain. The FRTSM0 diet-fed group also showed lower body moisture content and increased body protein content. The quadratic regression analysis revealed that digestive enzymes, nutrient digestibility, and serum biochemical parameters were optimized with less than 20% replacement of SM. Despite notable enhancements in nutritional status and a decrease in antinutritional factors, replacing SM with FRTSM did not emerge as a superior ingredient choice. However, it is important to highlight that a cautious replacement of 38% SM with FRTSM can be achievable in the Nile tilapia diet.